Nosocomial Infections in India: The Unaddressed Lacunae! - Bheemavarapu, Harika; Arief, Mohammad; Ahmad, Akram; Patel, Isha (Journal of Pharmacy Practice and Community Medicine)
A study by the international nosocomial infection control consortium found that the rates of hospital-acquired infections in India were higher than the statistics provided by the CDC (Center for Disease Control and Prevention). [1] Overcrowded hospitals with poor infrastructure, lack of basic hygiene, low healthcare professionals to patient ratio, inappropriate usage of invasive devices and antibiotics, and lack of regulation enforcement contributes to nosocomial infections-associated deaths in India. Recently, 290 children lost their lives in a tertiary referral hospital in Gorakhpur located in the northern state of Uttar Pradesh.[2] The Ministry of Health and Family Welfare of India launched an anti-microbial resistance awareness campaign known as ‘Red Line’, which encouraged people to put a stop to usage of medicines marked with a redline (antibiotics) and lacking a valid prescription from a physician.[3] In spite of awareness campaigns, the prevalence of nosocomial infections remains high in India. A recent study found 143 strains of Acinetobacter in a tertiary hospital in India, of which, 126 (88.1%) were extremely drug resistant.[4]